ESTUDO DA INTERAÇÃO DO GLIFOSATO COM BENTONITA DECORADA COM Eu3+ - KOCH, Camila dos Santos Rodrigues Marciano; TRENKEL, Fernanda Adriéli2 (fernanda_trenkel@hotmail.com; ARRUDA, Gilberto José (ANAIS DO ENIC, 2024)
-